Pengaruh Investment Opportunity Set (IOS), Likuiditas, dan Efisiensi terhadap Kualitas Laba: Studi Empiris pada Perusahaan Subsektor Perbankan yang Terdaftar di Bursa Efek Indonesia 2018-2021 - Luvia Rahmadani; Nelvirita Nelvirita (Universitas Negeri Padang, 2024)
This study aims to examine the effect of Investment Opportunity Set (IOS), liquidity, and efficiency on earnings quality. The data used is secondary data in the form of an annual report of commercial banks listed on the Indonesia Stock Exchange for 4 years of observation, from 2018 to 2021. The sample was determined by purposive sampling technique and then resulted in 42 companies as the sample. This research used multiple linear regression analysis models. These models were analyzed using EViews 12. The results of this study showed that investment opportunity set, liquidity, and efficiency have no effect on earnings quality.